2021
DOI: 10.1016/j.tcr.2021.100475
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic L4-L5 spondyloptosis with cauda equina syndrome: A case report

Abstract: Spondyloptosis at a lumbar level is usually encountered in an isthmic or a dysplastic types of spondylolisthesis. Post-traumatic lumbar spondyloptosis is comparatively a rare entity. As the injury involves a complete failure of all the osteo-ligamentous structures, it is highly unstable and has a high probability of a complete neurological deficit. On the contrary, the injury also has a lot of chances of meaningful neurological recovery if realignment and stabilization are done on an urgent basis. Here we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…When the patient was seen in the follow-up, he was recovered from the deficit. [ 8 ] Signs vary from asymptomatic patients with lower back pain to patients with neurological deficits up to cauda equina syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…When the patient was seen in the follow-up, he was recovered from the deficit. [ 8 ] Signs vary from asymptomatic patients with lower back pain to patients with neurological deficits up to cauda equina syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that neurological improvement requires surgical intervention to decompress and stabilize the spine. 4,8,11,13,14 There have been reports of successful closed reduction in spondyloptosis 12,15 and in partial lateral dislocation 16 ; however, reduction in lateraloptosis requires greater distraction forces because of the proximity of the involved vertebral bodies. 2,9 This case features several unique elements, including what the authors believe to be the first report of closed reduction for a case of lateraloptosis.…”
Section: Discussionmentioning
confidence: 99%